行星齿轮传动单侧板转臂的有限元分析 - 袁齐; 王勇 (Jixie chuandong)
One-sided plate pivoted arm in closed planetary gear transmission is normally integral.A method of processing the planetary gear shaft and the plate respectively and joining them in the way of interference fit to form a separated one-sided plate pivoted arm is studied.So that integral one-sided plate pivoted arms can be replaced and the manufacturability can also become easy.The structural analysis of assembled separated one-sided plate pivoted arm is conducted using finite element analysis software ANSYS considering the interference fit and the load on planetary gear shaft.The deformation and variation rule of stress as well as its distribution are revealed when the separated pivoted arm is joined with different magnitude of interference.As a result the optimum interference fit is obtained.The method of optimizing design of pivoted arm is feasible and the application effect is good.